Pengaruh Kualitas Produk Dan Nilai Pelanggan Terhadap Kepuasan Pelanggan di PT. Garuda Media Telematika Desa Kebondalem Kec. Bareng - Lina Ati Nurmaulida; Lilis Sugi Rahayu Ningsih (CV. ALIM'SPUBLISHING, 2023)
The decision to subscribe to the internet network at PT. Garuda Media Telematics, consumers consider product quality and ratings to get satisfaction. The company uses a cable network system (Fiber Optic) which has a speed compared to ordinary cable, which means that it can transfer data at high speed and the cost of installation and operation is relatively low. The method used in this study is a quantitative research method. The population used was 100 respondents, then the number of samples used in this study were 80 customers in 1 hamlet area using nonprobability sampling technique. The collection of data used in this research are observation, interviews, documentation, and questionnaires. Data analysis techniques using data quality test, classic assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that: (1) Product quality has no positive and significant effect on customer satisfaction at PT. Garuda Media Telematics Kec. With. (2) Customer Value indicates a positive and significant influence on customer satisfaction at PT. Garuda Media Telematics Kec. With. (3) Product Quality and Customer Value indicate that simultaneously have a positive and significant effect on customer satisfaction PT. Garuda Media Telematics Kec. Bareng. Keywords: Product Quality, Customer Value, and Customer Satisfaction